2019
DOI: 10.1002/nbm.4064
|View full text |Cite
|
Sign up to set email alerts
|

BOLD‐based cerebrovascular reactivity vascular transfer function isolates amplitude and timing responses to better characterize cerebral small vessel disease

Abstract: Cerebrovascular reactivity (CVR) is a dynamic measure of the cerebral blood vessel response to vasoactive stimulus. Conventional CVR measures amplitude changes in the blood‐oxygenation‐level‐dependent (BOLD) signal per unit change in end‐tidal CO2 (PETCO2), effectively discarding potential timing information. This study proposes a deconvolution procedure to characterize CVR responses based on a vascular transfer function (VTF) that separates amplitude and timing CVR effects. We implemented the CVR‐VTF to prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 59 publications
2
27
2
Order By: Relevance
“…Of the 142 articles reporting CVR measurements in pathology (referred to in Table 1), 70 studies assessed CVR to investigate pathophysiology, 48 studies explored the technical feasibility of a methodology to detect CVR impairment, 13 studies investigated the effect of a therapeutic intervention on CVR (surgical intervention for steno-occlusive diseases such as revascularisation, candesartan therapy for diabetes, bariatric surgery for obese subjects, haemodialysis for end-stage renal disease, therapeutic continuous positive airway pressure for obstructive sleep apnoea), six studies investigated the progression of pathologies, and five studies looked at the effect of CVR on fMRI BOLD activation. Relative to healthy controls, CVR was lower in patients in most of the pathologies (Krainik et al, 2005;Donahue et al, 2009;da Costa et al, 2016;Hartkamp et al, 2018;Thrippleton et al, 2018;McKetton et al, 2019) and CVR delays were longer in steno-occlusive diseases, small vessel disease and dementia (Hartkamp et al, 2012;Duffin et al, 2015;Thrippleton et al, 2018;Atwi et al, 2019;Holmes et al, 2020).…”
Section: Pathologiesmentioning
confidence: 75%
See 2 more Smart Citations
“…Of the 142 articles reporting CVR measurements in pathology (referred to in Table 1), 70 studies assessed CVR to investigate pathophysiology, 48 studies explored the technical feasibility of a methodology to detect CVR impairment, 13 studies investigated the effect of a therapeutic intervention on CVR (surgical intervention for steno-occlusive diseases such as revascularisation, candesartan therapy for diabetes, bariatric surgery for obese subjects, haemodialysis for end-stage renal disease, therapeutic continuous positive airway pressure for obstructive sleep apnoea), six studies investigated the progression of pathologies, and five studies looked at the effect of CVR on fMRI BOLD activation. Relative to healthy controls, CVR was lower in patients in most of the pathologies (Krainik et al, 2005;Donahue et al, 2009;da Costa et al, 2016;Hartkamp et al, 2018;Thrippleton et al, 2018;McKetton et al, 2019) and CVR delays were longer in steno-occlusive diseases, small vessel disease and dementia (Hartkamp et al, 2012;Duffin et al, 2015;Thrippleton et al, 2018;Atwi et al, 2019;Holmes et al, 2020).…”
Section: Pathologiesmentioning
confidence: 75%
“…The delay between two signals can be found using linear regression or cross-correlation by determining the time shift giving the best correlation between these two signals. As with CVR computation, delay computation is an evolving area and new methods are arising including obtaining the delay directly from the HRF between the BOLD signal and EtCO 2 (Atwi et al, 2019). One study corrected the hypercapnic delay for delay due to the vasculature (i.e., the delay it takes for the blood and CO 2 to travel from the lungs to the brain tissues) by using the BOLD delay from a hyperoxia challenge as a surrogate of vasculature delay and assuming no vasodilation due to hyperoxia (Champagne et al, 2019a).…”
Section: Cvr Data Processing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from BOLD-based CVR studies remain controversial [16]. Some studies reported whole brain CVR was not related to WMH [42,43], but others showed decreased CVR at baseline can predict the process of WMH lesions [18,44,45]. Based on previous studies, the current study con rmed that WMH was associated with decreased CVR again.…”
Section: Discussionmentioning
confidence: 48%
“…Impaired CVR is correlated closely with normal aging [13] and might be a sensitive early predictor of Alzheimer's disease [14]. In addition, it is reported that impaired CVR is the most reliable neuroimaging predictor of impending cerebrovascular disease [15,16], and could be a neuroimaging marker guiding the treatment and prevention of stroke and cerebral small vessel disease (CSVD) [17,18]. Furthermore, increasing evidences have demonstrated that CVR function is associated with subtle perfusion and microstructure changes in normal-appearing white matter (NAWM) [19], and has been involved in the pathophysiology disruption of the brain network connectome in individuals with WMH [20].…”
Section: Introductionmentioning
confidence: 99%